Perceived social support among Ministry of Interior officers - Majed, Mohammed Qais; Al-Shammari, Ahmed Hamza (Al-Adab Journal, 2021)
current study aims to identify the perceived social support among Ministry of Interior officers, and the differences in perceived social support among the Ministry of Interior officers depending on the variable of the military rank and the nature of work, and in order to achieve the objectives of the research, the researcher adopted the theory (House, 1981) of perceived social support. With the numbers of the Perceived Social Support Scale after reviewing the approved theory and previous studies, and its paragraphs amounted to (31) paragraphs, the psychometric properties of the scale, represented in honesty and consistency, were extracted and the scale applied to the research sample consisting of (400) officers from the Ministry of Interior in Baghdad Governorate and they were chosen by the random stratified method After collecting the data and processing it statistically by means of the Statistics Program (SPSS), the following results appeared: That the individuals of the research sample who are Ministry of Interior officers have a high perceived social support. There is a statistically significant difference in perceived social support according to the rank variable and in favor of a lieutenant colonel or higher, because their average is higher than lieutenant to major, and there is also a statistically significant difference according to the nature of work and for the benefit of the administrator because there is no significant interaction between the two variables (rank and work).